2017
DOI: 10.3390/ijms18040784
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme Associated Liposomal Gentamicin Inhibits Bacterial Biofilm

Abstract: Bacteria on living or inert surfaces usually form biofilms which make them highly resistant to antibiotics and immune clearance. Herein, we develop a simple approach to overcome the above conundrum through lysozyme-associated liposomal gentamicin (LLG). The association of lysozyme to the surface of liposomes can effectively reduce the fusion of liposomes and undesirable payload release in regular storage or physiological environments. The LLG was more effective at damaging established biofilms and inhibiting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…8 The SiO 2 -G nanohybrids thus possess superior antibiofilm effects compared with pristine gentamicin. A recent study 67 has reported a change in the surface charge of liposomal gentamicin from −54.5 to 17.5 mV after association with lysozyme and speculated the role of this surface charge in the antibiofilm effects of the lysozyme-associated liposomal gentamicin. The change in surface charge might facilitate an electrostatic attraction of the positively charged lysozyme-associated liposomal gentamicin to the negative charge of alginate in the biofilm matrix.…”
Section: Antibiofilm Effects Of Sio 2 -G Nanohybrids and Pristine Genmentioning
confidence: 99%
“…8 The SiO 2 -G nanohybrids thus possess superior antibiofilm effects compared with pristine gentamicin. A recent study 67 has reported a change in the surface charge of liposomal gentamicin from −54.5 to 17.5 mV after association with lysozyme and speculated the role of this surface charge in the antibiofilm effects of the lysozyme-associated liposomal gentamicin. The change in surface charge might facilitate an electrostatic attraction of the positively charged lysozyme-associated liposomal gentamicin to the negative charge of alginate in the biofilm matrix.…”
Section: Antibiofilm Effects Of Sio 2 -G Nanohybrids and Pristine Genmentioning
confidence: 99%
“…2014 ) and fluorescence microscopy (Hou et al . 2017 ). The biofilm biomass can also be determined by in vitro assays, such as the crystal violet staining method (Boda et al .…”
Section: Nanosystems Preclinical Validation: Biofilm Modelsmentioning
confidence: 99%
“…More recently, Hou et al . ( 2017 ) designed a gentamicin-loaded liposomal formulation with lysozyme surface functionalization. The cationic lysozyme was associated to the negatively charged liposome through electrostatic attraction.…”
Section: Lipid-based Nanosystemsmentioning
confidence: 99%
“…An ideal approach in this regard is to utilize two agents; one that penetrates/destroys the EPS matrix (such as lysozyme) and another to kill the individual bacteria within the biofilm (such as antibiotics) [17,18]. However, as we previously demonstrated through in vitro and in vivo biofilm analyses NS is unique in that it contains both activities [11].…”
Section: Resultsmentioning
confidence: 99%